2021
DOI: 10.1124/jpet.121.000695
|View full text |Cite
|
Sign up to set email alerts
|

Bosentan Alters Endo- and Exogenous Bile Salt Disposition in Sandwich-Cultured Human Hepatocytes

Abstract: Bosentan, a well-known cholestatic agent, was not identified as cholestatic at concentrations up to 200 µM based on the drug-induced cholestasis (DIC) index value, determined in a sandwichcultured human hepatocyte (SCHH)-based DIC assay. To obtain further quantitative insights into the effects of bosentan on cellular bile salt handling by human hepatocytes, the present study determined the effect of 2.5-25 µM bosentan on endogenous bile salt levels and on the disposition of 10 µM chenodeoxycholic acid (CDCA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(62 reference statements)
0
1
1
Order By: Relevance
“…Previously, a decrease in GCA and GCDCA content in the cell lysate, and a decrease GCA in the culture medium, have been reported upon 24 h bosentan-treatment with concentrations ranging from 10 to 100 μM in SCHHs (Lepist et al, 2014;Oorts, Van Brantegem et al, 2021), but we could not confirm this. No adverse effect of 24 h treatment with 50 μM bosentan (Burbank et al, 2017) or lopinavir on HepaRG cell viability was observed (current study).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Previously, a decrease in GCA and GCDCA content in the cell lysate, and a decrease GCA in the culture medium, have been reported upon 24 h bosentan-treatment with concentrations ranging from 10 to 100 μM in SCHHs (Lepist et al, 2014;Oorts, Van Brantegem et al, 2021), but we could not confirm this. No adverse effect of 24 h treatment with 50 μM bosentan (Burbank et al, 2017) or lopinavir on HepaRG cell viability was observed (current study).…”
Section: Discussioncontrasting
confidence: 88%
“…Fresh primary human hepatocytes are not readily available, but to overcome this limitation, cryopreserved primary hepatocytes can be obtained commercially. Primary hepatocytes, cultured either in sandwich or suspension, have been successfully used to study drugmediated inhibition of bile acid transport Oorts et al, 2021).…”
Section: Adverse Outcome Pathway Of Cholestasismentioning
confidence: 99%